Values Ngudi Kasampurnan Sunan Kalijaga As A Basis of Religious Moderation Education - Edris Zamroni; Gudnanto Gudnanto; Indah Lestari; Muslihati Muslihati (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Indonesia faces the challenge of infiltrating radical ideology, which tends to conflict and use religion to divide national life. This research explores the values